2007
DOI: 10.1002/marc.200700009
|View full text |Cite
|
Sign up to set email alerts
|

Block Copolymer Based Molecular Motor

Abstract: We propose a model of molecular motor based on diblock copolymer strongly adsorbed on a patterned surface. One of the blocks of the copolymer is modeled as field responsive. It is shown that time‐periodic collapse‐readsorption of the responsive block leads to the directed motion (reptation) of the molecule along the “track” provided by the surface pattern. Both the Langevin dynamics (LD) technique of computer simulation for the bead‐spring model and numerical solution of the Newton equations of a simplified (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This concept was confirmed by computer simulation methods. [311,312] Some other models on how to achieve autonomous propulsion using responsive polymers systems are reviewed in ref. [313] Our comb-like p(BPEM-g-nBuA) macromolecules shifted as a whole after many successive cycles of vapourstimulated conformational transitions.…”
Section: First Steps Towards Molecular Walkermentioning
confidence: 99%
See 1 more Smart Citation
“…This concept was confirmed by computer simulation methods. [311,312] Some other models on how to achieve autonomous propulsion using responsive polymers systems are reviewed in ref. [313] Our comb-like p(BPEM-g-nBuA) macromolecules shifted as a whole after many successive cycles of vapourstimulated conformational transitions.…”
Section: First Steps Towards Molecular Walkermentioning
confidence: 99%
“…[308][309][310] The concept of 'molecular walker' on the basis of responsive macromolecular objects was also known from the literature. [175,311] According to the concept, stimulated directional motion of macromolecular objects on a substrate may be achieved as a result of many induced cyclic conformational transitions provided there is some asymmetry in the macromolecular structure and there are some oriented 'rails' on the surface. This concept was confirmed by computer simulation methods.…”
Section: First Steps Towards Molecular Walkermentioning
confidence: 99%
“…An increase in the surface pressure led to rod–globule transition at the end of the brush with a higher grafting density, thus leading to tadpole-like form of the comb molecules. This kind of molecule may serve as a molecular motor by analogy with the directional movement of diblock copolymers [ 120 ]. Computer simulations demonstrated that diblock copolymer adsorbed on a striped surface can shift preferentially in one direction if one of the blocks undergoes periodic collapse and readsorption [ 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…This kind of molecule may serve as a molecular motor by analogy with the directional movement of diblock copolymers [ 120 ]. Computer simulations demonstrated that diblock copolymer adsorbed on a striped surface can shift preferentially in one direction if one of the blocks undergoes periodic collapse and readsorption [ 120 ]. In the case of combs, a difference in the desorption properties between the sparsely and densely grafted ends may have the same effect on the movement [ 4 , 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, biological molecular motors with a characteristic size on the order of nanometers operate under a stationary direct current (DC) voltage. 2 Despite these examples in Nature, it is still difficult to fabricate electrical motors on a sub-millimeter scale.…”
Section: Introductionmentioning
confidence: 99%